OS CONTEXTOS E OS CONTRASTES DA EDUCAÇÃO BRASILEIRA: A EDUCAÇÃO POPULAR E AS DEMANDAS POR UMA EDUCAÇÃO DE QUALIDADE - Fábio Mariano da Paz; Yoshie Ussami Ferrari Leite (Universidade do Oeste Paulista, 2012)
This text anchored on a qualitative approach, aims to put in discussion the meanings that are attributed to the Brazilian public school crisis and the growing discourse about the loss of quality. For this, lists the major historical and social transformations through which the country passed from the colonial period to the present, to emphasize that the massification of the school, although it is constantly blamed for the weakening of teaching, currently represents the legitimacy of a new time history, in which the population of achievement like never before in the course of history, one of its main social rights. Also addresses the impacts of the changes caused by the expansion of education and the different perspectives that can be applied to the analysis of the quality standards of today, as well as new responsibilities assumed by the public school to account for the needs and social deprivation accumulated over centuries by the absence of an active state.